(untitled) (Fiep Bulletin - online, 2012)
In Brazil, the population of elderly has growing in recent years, representing 10% of the whole population. To the extent in which the population aging occurs, it is observed the utilization of the hospital services by this public with greater frequency than the other age groups, resulting in greater costs for the hospital services. This implies on the prolongation of treatment and on the slow recuperation, increasing the susceptibility for the development of complications like pressure ulcers, which are skin injuries characterized by ischemia and tissue necrosis due to the prolonged compression of soft tissues between bony prominences and the external surface. Objectives: to characterize the profile of the elderly who developed pressure ulcer during hospitalization. Methodology: exploratory-descriptive study, retrospective, with quantitative approach, realized in João Pessoa-PB, from January to December, 2009. The population was constituted by all the hospitalized patients in the period, and the sample was composed by 46 elderly aged over 60 years and that developed pressure ulcer. The project was analyzed and approved by the Research Ethics Committee of Santa Emilia de Rodat College (FASER), under number 034/2010, obeying the Resolution 196/96 of the National Health Council. Results: In the studied period, 46 elderly developed PU during hospitalization, 54.4% of them were men and 45.7% were women. The predominant sample was over 80 years (43.6%), with length of hospitalization between 16 and 30 days (41.3%), and that developed PU in the first 15 days (67.4%). The sacral region was the most affected by the injuries (82.6%), with evolution of 37% for stages I and II, each. Conclusion: it is emphasized the need for a greater attention to this group of population who, in frank expansion, necessitates professionals that are sensitive, trained and aware of the possible complications which may ensue during hospitalization.